Problematika dan Upaya Penanganan terhadap Penyandang Disabilitas Mental : ODGJ dan Down Syndrome - Sustian Alfina; Rizki Ananda Agust Lailita; Dwi Sriwidadi; Rahayu Mardikaningsih; Mila Hariani; Eli Masnawati; Yeni Vitrianingsih; Yuliastutik Yuliastutik; Nelud Darajaatul Aliyah; She Fira Azka Arifin; Roidatus Shofiyah; Febriarsita Eka Sasmita; Mirza Elmy Safira (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
People with mental disabilities, especially people with mental disorders (ODGJ) and individuals with Down Syndrome, face significant challenges in their daily lives. This journal explores the main problems they face. The purpose of this community service activity is to identify problems and solutions that must be taken for people with mental disabilities. The empowerment method used in this community service activity is the ABCD (Asset Based Community Development) method. This journal proposes several strategic efforts to overcome these problems. Increasing public awareness through education and counseling can help reduce stigma. Strengthening mental health services by increasing access and quality of services is essential. Support for inclusive education and vocational training for people with mental disabilities can improve their skills and job opportunities. Psychosocial support and family training are also very important to help care for family members with mental disabilities. Collaboration with various parties is also needed to create an inclusive and supportive environment for people with mental disabilities. They can live better and have equal opportunities to contribute to society through the right solutions.